2017
DOI: 10.7595/management.fon.2017.0012
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle of Quality Management System in Organizations

Abstract: Considering that some organizations implemented the ISO 9001 standard more than 25 years ago, while othersdid it a while ago, some quality management systems (QMS) are older than others. This fact led authors to question whether there are differences between long and recently implemented quality management systems. Is there a pattern that QMS follows in its aging that could be considered as a life cycle of QMS? From October 2013 to June 2014, authors have conducted a survey in 186 certified companies using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In both groups of companies (those with fully implemented QMS and those with partially implemented QMS), different benefits and disadvantages are expected to appear in earlier years of QMS implementation than those that would appear in later years of QMS application. This contributes to the findings of Živaljević et al. (2017) that QMS changes through time.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In both groups of companies (those with fully implemented QMS and those with partially implemented QMS), different benefits and disadvantages are expected to appear in earlier years of QMS implementation than those that would appear in later years of QMS application. This contributes to the findings of Živaljević et al. (2017) that QMS changes through time.…”
Section: Discussionsupporting
confidence: 70%
“…There are researches on the changes in QMS characteristics through time which show that QMS has different features in earlier than in later years of its implementation (see: Morsal et al. , 2009; Novokmet and Rogošić, 2017; Sfreddo et al ., 2018; Zaloha et al ., 2018; Živaljević et al ., 2017; Ginevič ius et al ., 2015). Therefore, it is expected that benefits and disadvantages of young and mature QMS would differ as well.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Andre et al, 2009;Asif and Searcy, 2014;Asif, Searcy, Zutshi and Ahmad, 2011;Domingues et al, 2016Domingues et al, , 2017Cabecinhas et al, 2017;Ejdys and Matuszak-Flejszman, 2010;Ferreira and Gerolamo, 2016;Fresner and Engelhardt, 2004;Gianni et al, 2017;Hadad, 2017;Hernandez et al, 2016;Jørgensen, 2008;Llonch et al, 2018;Mežinska et al, 2015;Oskarsson and Malmborg, 2005;Qi et al, 2013;Rebelo et al, 2014Rebelo et al, , 2016Rocha and Searcy, 2012;Rocha et al, 2007;Roslin et al, 2017;Santos et al, 2012;Tsai and Chou, 2009;Zeng et al, 2011). Qi et al (2013) and Rebelo et al (2016), in line with several authors (such as Domingues et al, 2016;Hernandez et al, 2016;Gianni et al, 2017), found that the three dimensions (economic, environmental and social) usually ascribed to SD establish a connection with three MSs (QMS, EMS and OHSMS) that, in turn, also support the standards requirements (core of the resulting IMS) (Almeida et al, 2014;Domingues et al, 2016Domingues et al, , 2017Ezzat et al, 2017;Fonseca and Domingues, 2017;Rebelo et al, 2016;Sampaio et al, 2012;Simon et al, 2011;Živaljević et al, 2017, s...…”
Section: Introductionmentioning
confidence: 60%